CHINA’S DIPLOMATIC AND SECURITY THEORIES IN THE NEW ERA - Yang Jiemian (Сравнительная политика, 2019)
The 18th CPC Congress marked a new era for China’s domestic and foreign policies. Building on traditional Chinese culture and Marxism, Chinahas achieved remarkable progress in diplomatic theory building in terms of theoretic framework, issue orientation, and methodologies, and now it is now time for systematic integration. While preparing for the CPC 19th Congress, we should heighten consciousness of practice and theory, enhance issue awareness, grasp the essence of the matters, conduct analytic researches, and work at effective solutions, and stress summarization and crystallization, thus forming new concepts and theories. While buildingChina’s system of diplomatic theories, it is necessary to better align foreign policy with security and domestic policies; integrate diplomatic philosophy, theories, strategies, and policies; properly handle the relationships between Chinese characteristics, international relevance, and worldwide significance; and increase the applicability of theories in diplomatic practice.